SAVI and RME Learning Models to Improve Mathematical Problem Solving Skills - Siswadi Siswadi; Lilis Lilis; Yumira Simamora (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Realistic mathematics is a very important approach that links the real world with student learning activities. This quantitative study aims to obtain information related to improving the SAVI learning model with RME on students' mathematical problem solving abilities. This research involved 60 students (30 students VIIIc and 30 students VIIIa) who were positioned as research subjects. Students' mathematical problem solving abilities were collected using a rubric in the form of an essay consisting of 5 questions. The collected data was tested using the t-test. The results of this study inform that students' problem solving abilities on cube and cuboids with RME learning are better than students who follow SAVI learning in class VIII students of MTs Nurul Iman Tanjung Morawa Deli Serdang.